Guidance for studies evaluating the accuracy of biomarker-based nonsputum tests to diagnose tuberculosis - Drain, Paul K.; Denkinger, Claudia M. (The journal of infectious diseases, 2019)
Abstract. The World Health Organization’s (WHO) “End TB” strategy calls for development and implementation of novel tuberculosis (TB) diagnostics. Sputum-based